2021
DOI: 10.1002/mar.21613
|View full text |Cite
|
Sign up to set email alerts
|

Collectivism fosters preventive behaviors to contain the spread of COVID‐19: Implications for social marketing in public health

Abstract: Apart from personal‐ and societal‐level factors, we propose that collectivism also plays a role in the spread of COVID‐19. Results from six studies using both secondary datasets and laboratory experiments conducted in two different countries demonstrate that collectivism is: (a) negatively associated with the spread of COVID‐19 and (b) positively associated with the self‐importance/expectation to engage in widely publicized behaviors to prevent the spread of the disease, as well as with greater likelihood to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Future research should test additional reasons why scarcity reduces the sense of priority and willingness to receive a vaccine. For example, different reasons such as prosociality, motivated reasoning, and feelings of powerlessness and resignation may operate simultaneously, and individual as well as societal factors, such as collectivism (Cho et al, 2021), must be considered holistically. Furthermore, in Study 2, we used a one‐item measure for compassion for individuals in high‐risk groups for COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should test additional reasons why scarcity reduces the sense of priority and willingness to receive a vaccine. For example, different reasons such as prosociality, motivated reasoning, and feelings of powerlessness and resignation may operate simultaneously, and individual as well as societal factors, such as collectivism (Cho et al, 2021), must be considered holistically. Furthermore, in Study 2, we used a one‐item measure for compassion for individuals in high‐risk groups for COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Collectivism was even cited among lay members of the public in qualitative research examining the prevention behaviors of Chinese–Canadians during the early wave of the COVID-19 pandemic (Lee et al, 2021 ) – giving face validity to the hypothesized link between collectivism and prevention behavior. These are further supported with individual-level quantitative research showing that greater collectivism is associated with more support for and uptake of COVID-19 prevention behaviors (Bok, Shum, Harvie, & Lee, 2021 ; Cho, Guo, & Torelli, 2022 ; Lu, Jin, & English, 2021 ; Travaglino & Moon, 2021 ; Yu, Lau, & Lau, 2021 ). Greater collectivism has also been shown to be correlated with fear of COVID-19 (Ahuja, Banerjee, Chaudhary, & Gidwani, 2021 ; Germani, Buratta, Delvecchio, & Mazzeschi, 2020 ).…”
Section: The Role Of Individualism–collectivism In the Covid-19 Pandemicmentioning
confidence: 67%
“…Third, the data in the current study is silent on the underlying mechanisms of cultural influence on guideline compliance. Mediation analysis in previous studies revealed that collectivism led to self-report guideline compliance because collectivist individuals (1) were more concerned about others ( 10 ), were more likely to perceive guideline compliance as a normative behavior that was considered as important by others ( 5 , 6 ), trusted the government more ( 21 ), and felt less powerlessness (i.e., the sense of being unable to make a meaningful impact on important issues) ( 22 ). Collectivistic orientation has also been linked with higher perceived risk of infection ( 23 ), which might be another mediator of cultural influence on guideline compliance because people may incline to reduce outside activities if they worry about being infected.…”
Section: Discussionmentioning
confidence: 99%
“…For example, collectivist cultures led to slower increase in prevalence rate and mortality rate within a 30-day timeframe after a region's lockdown (4). Over a longer period, such as the first three months from the first reported case or the whole year of 2020, a positive correlation between regional collectivism and COVID-19 prevalence and mortality has also been consistently found, showing that less cases of infection and death were reported in more collectivist regions (5)(6)(7)(8)). Such regional differences may partly result from people's guideline compliance, such that people with more collectivist orientation were more willing to comply with governmental guidelines and engage in preventive behaviors such as mask wearing and social distancing (5,6,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 94%